Peranan Sekretaris Camat dalam Membantu Tugas Camat pada Bidang Kepegawaian di Kecamatan Medan Timur - Aprilia, Anggi; Suharyanto, Agung; Angelia, Nina (Universitas Medan Area, 2024)
The role of the Sub-District Secretary in Assisting the Sub-District Head Tasks in the Personnel Sector in the District of East Medan, where the Sub-District Secretary has the role of continuing tasks and programs and overcoming problems to facilitate the implementation of activities in the Personnel Sector. The purpose of this study was to determine the role of the Sub-District Secretary in Assisting the Sub-District Head Tasks in the Personnel Field, and the obstacles faced by the Sub-District Secretary in Assisting the Sub-District Head Tasks in the Personnel Sector in the District of East Medan. As for the problems, namely regarding delays in coordinating tasks with employees, lack of employee initiative, dominant decisions taken by the Sub-District Head, and lack of direct inspections of employees. To approach the problem, aspects of Sondang P. Siagian (2012) are used, including interpersonal, informational, decision-making, and supervisory roles. Data was collected based on data collection techniques with observation, interviews, and documentation, and analyzed qualitatively with a descriptive nature. The results showed that the role of the Sub-District Secretary in Assisting the Sub-District Head Tasks in the Personnel Sector could be said to be good in terms of the interpersonal role where there was direction and motivation given to employees, then the informational role by using two-way communication both in conveying and receiving suggestions. decisions made by way of deliberation, as well as the role of supervision, carried out directly through attendance and supervision, or indirectly through online attendance and e-performance